Estímulo ao aumento do volume de operações financeiras por parte dos cooperados de uma cooperativa de crédito segmentado - Becker, Márcio Daniel (Universidade do Vale do Rio dos Sinos, 2025)
The general objective of this research was to propose alternatives to stimulate an increase in the volume of financial transactions by members of a Segmented Credit Cooperative. The specific objectives were to analyze the portfolio of services provided by the Cooperative to its members; to identify the reasons why members remain members of the Cooperative; and to analyze the factors that hinder a greater volume of financial transactions by members with the Cooperative. Credit unions play a crucial role in the global economy, often responsible for the social and economic-financial inclusion of an entire community by establishing organized societies that provide services to their members (or members). By means these organizations, members aim to achieve their goals, using cooperation and mutual aid as crucial elements. The research adopted a qualitative approach, grounded in, semi-structured individual interviews with the membership and employees. A total of 22 interviews were conducted, with 10 interviewees being active members, 8 interviewees being inactive members, and 4 interviewees being employees of the institution under study. Data obtained from the interviews revealed that the cooperative occupies a secondary position in the financial lives of most members, thus revealing a low priority regarding the use of its products and services. It also became clear how much the negative experience associated with bureaucracy and lack of autonomy in processes directly impacts this result. Portfolio diversification presented itself not only as a growth opportunity but also as a loyalty strategy, by offering solutions more aligned with the expectations of the target audience. The absence of this product, as well as others, limits the Cooperative's ability to position itself as a comprehensive institution, capable of meeting the broader financial protection needs of its members. A significant share of the members is inactive, meaning they are not using any of the Cooperative's Products and Services or any of its financial solutions. The lack of use of these products and services occurs largely due to misinformation; the informational vacuum that limits the potential for expanding the financial relationship between the parties. For a public increasingly accustomed to fast, intuitive digital solutions, any sign of slowness or the need for intermediation represents a significant barrier. Ultimately, it’s possible to conclude that, beyond operational issues, there’s a strategic repositioning challenge. The Cooperative needs to align its service structure and internal processes with a more agile model, investing in digital channels that increase member autonomy and reduce not only the perception of bureaucracy, but its actual existence. From the research, suggestions for improvements were presented, divided into four central areas: Cooperative Training and Education, Technology and Digital Channels, Service Portfolio, Communication and Relationships.
Keywords: Cooperativismo; Cooperativas de crédito; Serviços financeiros; Operações financeiras; Prática relacional; Relacionamento com clientes; Cooperativism; Credit cooperatives; Financial services; Financial operations; Relational practice; Customer relationship; ACCNPQ::Ciências Sociais Aplicadas::Administração